The effects of perceptual-cognitive training on subjective performance in elite athletes - Moen, F.; Hrozanova, M.; Pensgaard, A. M. (The Sport Journal, 2018)
This current study examines if a perceptual-cognitive training program, such as the Neurotracker (NT) 3-dimensional (3D) multiple object tracking (MOT) device, has the potential to improve elite athletes` performances in dynamic sports. Fifty-four elite athletes from boxing, wrestling, women handball, women soccer, orienteering, biathlon, alpine skiing, sled hockey, badminton and table tennis completed a pre-post quasi experiment over a period of 5 weeks (46% males and 54% females). The results show that the NT baseline scores and subjective performance improved significantly during the experiment. However, subjective performance improved only when learning rate and number of targets were controlled for. The results are discussed in regard of applied implications and possible future research.